Child Outcomes for Mothers Facing Trial (COMFT): Protocol for a multi-national data linkage study to understand caregiver arrangements for children of mothers involved in the criminal and family justice systems - Broadhurst, Karen; Alrouh, Bachar; Humphreys, Leslie; Cowley, Laura; North, Laura; Tranter, Kathryn; Hargreaves, Claire; Mizen, Amy; Griffiths, Lucy (International Journal of Population Data Science, 2026)
Background An unknown proportion of mothers are involved in both the Criminal Justice and Family Justice Systems. Mothers with cross-justice involvement are at risk of losing their children from their care on a temporary or permanent basis. Objectives Speaking directly to the Female Offender Strategy for England and Wales and the imperative to preserve mother-child relationships wherever safe and in the child's best interests, the Child Outcomes for Mothers Facing Trial (COMFT) study aims to uncover mothers' dual system involvement and provide vital insights about caregiver outcomes for children. The project will use administrative data to deliver the first-ever quantitative analyses of mothers and children at the intersection of the criminal and family justice systems. Methods The project will link female defendant records in England and Wales to mother and child family court records (public and private law), as well as demographic data. Data will be accessed through the globally leading Secure Anonymised Information Linkage (SAIL) Databank at Swansea University. The proposal has been developed collaboratively with project partners, committed to transforming justice outcomes for women and children, including the Ministry of Justice (MoJ), the Children and Family Court Advisory and Support Service (Cafcass), Cafcass Cymru and the leading charity, Birth Companions. Formal ethical approval has been granted by the Universities involved. Patient and Public Involvement A unique feature of this project is that from design to completion, a group of mothers with lived experience are directly involved. The 'COMFT-Together' advisory group ensures that the perspectives of women with cross-justice involvement inform this study, and that mothers benefit directly from a shared research role and curriculum facilitated by Birth Companions. Implications As the study is the first of its kind, it will also serve as an international exemplar, relevant to policy makers across the globe wishing to use routine organisational data to inform public services delivery.